RESEARCH ON BILINGUAL EDUCATION IN TAIWAN’S HIGH SCHOOLS: Received: 07th November 2023; Revised: 20th December 2023, 26th December 2024; Accepted: 29th November 2023 - Kuo, I-Hsuan; Hsueh, Tung-Fu; Kuo, Dr. Chiu-Cheng (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study aims to explore the current status of bilingual education implementation in high schools in Taiwan. This study formulated interview topics based on different aspects of bilingual education and interviewed six relevant personnel through the literature analysis and qualitative in high schools. It included principals, teachers and students in order to understand the impact of bilingualism on the influencing factors and implementation difficulties. The conclusions drawn are as follows: First. Bilingual education policies and supporting measures will affect the progress and implementation effectiveness of bilingual education. second. It is helpful for schools to set clear bilingual education goals. third. There are differences in the effectiveness of bilingual education for students in general high schools and technical high schools. Fourth. The preparation of bilingual teachers and the community are the key to the success of bilingual education. fifth. Creating an immersive learning environment can improve the effectiveness of bilingual teaching. sixth. The urban-rural gap and insufficient resources are major obstacles to promote bilingual education. seventh. If teacher spend too much time on teaching English, it will affect students ‘acquisition of professional subject knowledge. eighth. Bilingual teaching causes burden on teachers and affects their willingness to promote it.